Effects of a function-based intervention on children´s school refusal behavior in Iceland - Ásdís Halla Einarsdóttir 1995- (2022)
School refusal is a problem in Iceland and if non-attendance goes over certain criteria child protective services (CPS) must be contacted. The School-Refusal Assessment Scale- Revised (SRAS-R) is a scale that assesses school refusal behaviors with a function-based approach. The present study investigated the effects of a function-based intervention on children ‘s school refusal behavior in Iceland. Participants were 3 children who emitted school refusal behaviors prior to school in the mornings. Parents, children, and their teachers did an open-ended interview, and parents and their children answered the SRAS-R to assess the function of the school refusal behaviors. The results from the open-ended interviews and SRAS-R were used to formulate an individualized intervention package for each participant. Every participant got a contingency contract with a visual schedule connected to a token system. In addition, parents got a list of how to respond to each school refusal behavior emitted by their child in the mornings. Finally, one participant got a changed after-school routine and a list of tasks to help him communicate to peers. School refusal behavior for all participants decreased after the intervention package was introduced. Parents and their children answered a social validity questionnaire after the study and reported that the intervention was easy to implement, fun for the children and resulted in a better morning routine and that the children felt better after receiving the intervention. Keywords: School-refusal, Problem behaviors, School refusal assessment scale, SRAS-R, nonattendance, school.